2007
DOI: 10.1037/0022-006x.75.2.285
|View full text |Cite
|
Sign up to set email alerts
|

Personalized mailed feedback for college drinking prevention: A randomized clinical trial.

Abstract: The current study was designed to evaluate the efficacy of a mailed feedback and tips intervention as a universal prevention strategy for college drinking. Participants (N = 1,488) were randomly assigned to feedback or assessment-only control conditions. Results indicated that the mailed feedback intervention had a preventive effect on drinking rates overall, with participants in the feedback condition consuming less alcohol at follow-up in comparison with controls. In addition, abstainers in the feedback cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
258
4
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 270 publications
(296 citation statements)
references
References 53 publications
32
258
4
1
Order By: Relevance
“…It is worth noting that the intervention did not significantly reduce alcohol-related problems overall (Neighbors et al, 2004), which is not atypical for brief interventions (e.g., Collins et al, 2002;Larimer et al, 2007;Walters et al, 2007). Individuals who drink to cope may require a more intensive intervention tactic (e.g., cognitive-behavioral therapy) that focuses on their motivations for drinking.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the intervention did not significantly reduce alcohol-related problems overall (Neighbors et al, 2004), which is not atypical for brief interventions (e.g., Collins et al, 2002;Larimer et al, 2007;Walters et al, 2007). Individuals who drink to cope may require a more intensive intervention tactic (e.g., cognitive-behavioral therapy) that focuses on their motivations for drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Given that a .01 increase in daily eBAC was associated with a 7% increase in odds of perpetrating dating violence, reducing the number of drinks consumed during heavy drinking episodes will significantly reduce the likelihood of perpetrating dating violence. To do this, individuals could be taught protective behavioral strategies, such as alternating alcoholic beverages with nonalcoholic beverages, slowing the pace of drinking, or setting a drinking limit that they agree not to exceed (Larimer et al, 2007;Martens et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, despite the availability of PBS to mitigate the negative effects of drinking alcohol, alcohol consequences are still prevalent on college campuses. Some have identified college students experiencing depression as an at-risk group for alcohol problems (e.g., Geisner et al, 2007). However, although researchers have considered the relationship between depression, anxiety, and alcohol behaviors (e.g., Martens et al, 2008;Shoal et al, 2005), there has been a lack of research on the specific cognitions associated with depression (i.e., rumination) and anxiety (i.e., worry).…”
Section: Current Studymentioning
confidence: 99%
“…Gollust, Golberstein, and Hefner (2007) found that 15.6% of college students had either an anxiety or depressive disorder, based on DSM-IV-TR criteria. Although the findings are mixed as to whether there is a difference in alcohol consumption between depressed and nondepressed students (Fabiano et al, 2009;Pedrelli et al, 2010), depressed students are considered an at-risk group for problem drinking (Geisner, Neighbors, Lee, & Larimer, 2007). For example, depressed students who drink are more likely to experience negative alcohol consequences compared to non-depressed students who drink (Camatta & Nagoshi, 1995;Gonzalez, Reynolds, & Skewes, 2011).…”
Section: Mental Health Among College Studentsmentioning
confidence: 99%
See 1 more Smart Citation